Strengthening the Psychological Aspects of Autistic Children through Islamic Learning Methodology - Hidayat, Lutfiadji Agung; Rahmatullah, Azam Syukur; Aziz, Akbar Nur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to provide an overview of Islamic learning suitable for children with autism and the urgency of educators in using Islamic learning models. This study uses the Systematic Literature Review (SLR) method with data sources from journals, books, and other sources on related topics. The results of this study indicate that the Islamic learning methodology for children with autism can be carried out using the Islamic habituation model, Talaqqi wa Musyafahah, and Al-Quran Therapy. However, other methods include ABA, TEACCH, Son-Rise, Music Therapy, and Picture Exchange Communication Systems. However, regardless of the form or model of the method offered, as is the case with learning in general, the key factors supporting learning in children with autism are the availability of qualified teachers equipped with certified practices and materials, integrated teaching curricula, facilities, and training. Learning facilities in the school environment. Audio-visual form. The availability of professionals who can meet the learning needs of autistic children is not enough.